PREVENTION AND ENFORCEMENT EFFORTS AGAINST CRIME EMBEZZLEMENT POLICE CAR RENTAL IN RESORT CITY OF SEMARANG (Case Study No. Bp / 87 / K / Bap / VII / 2018 / Reskrim on 6 June 2018) - Insan Al Ha Za Zuna Darma Illahi; Ira Alia Maerani; Aryani Witasari (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This study aims to identify and explain the efforts to control and enforcement of laws against the crime of embezzlement of car rental in City Police Large Semarang in Case Number: Bp / 87 / K / Bap / VII / 2018 / Reskrim on 6 June 2018, to provide educational material or contributing to the entrepreneur car rental and Police Large city Semarang in prevention and law enforcement against criminal acts of embezzlement of car rental in the city of Semarang, and to investigate and explain the constraints and find solutions in the response and enforcement of laws against the crime of embezzlement car rental Big City Police in Semarang.This study uses empirical juridical approach or legal research Sociological with embezzlement case study specification car in Semarang. Data were collected from documents and interviews with investigators Vice Unit I resum Sat Criminal Police Large City Semarang to then analyzed using qualitative analysis, then concluded.The results showed that law enforcement is often done by the City Police of the Semarang to the crime of embezzlement car rental, while the factors that are the cause has not done of law enforcement due to limits in the Book of the Law of Criminal Law and the crime on complaint, therefore efforts conducted by the City Police of the Semarang can be divided into three attempts pre-emptive, preventive and repressive, these efforts are sometimes subject to constraints such as the difficulty of giving meaning to the people, cars rented a car loan, easy to hand over vehicles to consumers.Keywords: prevention efforts by law enforcement, the crime of embezzlement.